Perinatal Protein Undernutrition and Cardiovascular System: A Systematic Review - Xavier, José Emerson; Antonio, Erivaldo Alves; Oliveira, Lisiane dos Santos; de Souza, Sandra Lopes; de Medeiros, Juliana Pinto; Lima, Lavínia Calmon; de Carvalho Fraga, Carlos Alberto; da Silva Miguel, Rafael Danyllo (Journal of Morphological Sciences, 2018)
The present study is a systematic review of the literature that aimed to characterize the profile in animal models used to study perinatal protein malnutrition correlating with the cardiovascular system and the implications of malnutrition to the heart. Therefore, an extensive search was conducted in the PubMed, BVS, and SciELO databases, using combinations of the descriptors protein malnutrition, pregnancy, heart, lactation, and cardiovascular system. A total of 247 articles were found, but after excluding duplicities and applying the inclusion/exclusion criteria, only 12 papers remained. The analysis of the results shows that the diet used in the studies has a protein content of between 17 and 22% for the control animals, and of between 0 and 9% for the animals submitted to perinatal protein malnutrition. The main morphofunctional changes observed in the cardiovascular system are related to high blood pressure, increased apoptosis of cardiomyocytes, and reduction in the absolute size of the heart, among other ultrastructural and molecular changes.
Keywords: cardiovascular diseases; heart; offspring; undernutrition